2004
DOI: 10.1159/000076456
|View full text |Cite
|
Sign up to set email alerts
|

Does Meeting Needs Improve Quality of Life?

Abstract: Background: This study investigated the relationship between patient-rated unmet needs and subjective quality of life using routine outcome data. Methods: 265 mental health service patients from South Verona were assessed using the Camberwell Assessment of Need, the Lancashire Quality of Life Profile, and other standardised assessments of symptoms, disability, function and service satisfaction. At 1-year follow-up, 166 patients were still in contact, of whom 121 patients (73%) were re-assessed. Results: Higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
76
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(94 citation statements)
references
References 18 publications
10
76
1
5
Order By: Relevance
“…Our main longitudinal finding is that QOL at baseline accounted for 40% of variance in the same factor at follow-up. This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up.…”
Section: Longitudinal Findingssupporting
confidence: 89%
“…Our main longitudinal finding is that QOL at baseline accounted for 40% of variance in the same factor at follow-up. This is consistent with other longitudinal studies done in different clinical samples (Slade et al, 2004;Hansson and Bjorkman, 2007). Moreover, Landolt et al (2012), using a SEM approach in a groups of patients with a first-episode of schizophrenia, found that fewer unmet needs, higher depression, baseline QOL, age and gender (female) were all factors associated with higher QOL at follow-up.…”
Section: Longitudinal Findingssupporting
confidence: 89%
“…This hypothesis has been investigated in rather few, mainly cross-sectional studies, showing an robust association between more unmet needs and a worse subjective quality of life (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the meeting of spiritual needs has been shown, under some circumstances, to relate to positive mental health treatment outcomes (Cornah, 2006). One study which explored the relationship between community mental health service user need and quality of life found that high levels of service user-rated unmet need were associated with low subjective quality of life (Slade, Leese, Ruggeri, Kuipers, Tansella and Thornicroft, 2004). This association was found not only to be sustained over time but also enabled prediction of subjective quality of life at one-year follow-up.…”
Section: Domains Of Needmentioning
confidence: 99%